2006
DOI: 10.1002/humu.20336
|View full text |Cite
|
Sign up to set email alerts
|

Mean age-of-onset of familial alzheimer disease caused by presenilin mutations correlates with both increased Aβ42 and decreased Aβ40

Abstract: The varied ways in which mutations in presenilins (PSEN1 and PSEN2) affect amyloid b precursor protein (APP) processing in causing early-onset familial Alzheimer disease (FAD) are complex and not yet properly understood. Nonetheless, one useful diagnostic marker is an increased ratio of Ab42 to Ab40 (Ab42/Ab40) in patients' brain and biological fluids as well as in transgenic mice and cells. We studied Ab and APP processing for a set of nine clinical PSEN mutations on a novel and highly reproducible enzyme-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
260
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(287 citation statements)
references
References 54 publications
22
260
3
2
Order By: Relevance
“…In addition, we observed that a variety of FAD-associated PS1 mutations resulted in overproduction of Aβ43 in a manner correlating with the quantity of Aβ42 as well as with the age of onset of the patients 24 ( Fig. 5 and Supplementary Fig.…”
Section: Aβ Pathology and Memory Impairment Of App Tg Micementioning
confidence: 88%
See 2 more Smart Citations
“…In addition, we observed that a variety of FAD-associated PS1 mutations resulted in overproduction of Aβ43 in a manner correlating with the quantity of Aβ42 as well as with the age of onset of the patients 24 ( Fig. 5 and Supplementary Fig.…”
Section: Aβ Pathology and Memory Impairment Of App Tg Micementioning
confidence: 88%
“…Because Aβ42 is produced independently of Aβ43 in the presence of γ-secretase, some of the FAD-associated PS1 mutations that cause a decrease in Aβ40 without an increase in Aβ42, such as A79V, A231V, C263F, L282V, L166P and G384A 24,38 , might actually result in the elevation of Aβ43 in a manner similar to the R278I mutation. In addition, PS1-ΔE10, an artificial PS1 mutation located to the loop domain of PS1 where R278I is present, showed a significant reduction of the steady state levels of Aβ40 without any alteration of the Aβ42 levels similar to our results, however Aβ43 levels were not measured 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The g-secretase complex with the I143T mutation in PSEN1 has been suggested to produce Ab peptides of different lengths. 13 We recently reported that a longer variant, Ab43, is present in plaque cores and in total amyloid preparations obtained from sporadic and familial AD brains, and was indeed found more frequently than Ab40. 14 A quantitative approach was used to study Ab40, Ab42, and Ab43 in two mutation carriers diagnosed with a severe and aggressive form of EOAD by examining samples taken from six brain regions, including the frontal, parietal, temporal, and occipital cortex, as well as anterior hippocampus and cerebellum.…”
Section: Introductionmentioning
confidence: 91%
“…Aβ 42 has a higher propensity to form prefibrillar and fibrillar aggregates than Aβ 40 and has also been reported to be more toxic [4]. Furthermore, it has been shown that an increased ratio of Aβ 42 to Aβ 40 correlates with an increased risk of subsequently developing AD [5]. Monomeric Aβ aggregates into insoluble fibrils via different soluble intermediates [6].…”
Section: Introductionmentioning
confidence: 99%